The Optical Polaron in Spherical Quantum Dot Confinement - Zher Samak; Bassam Saqqa (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The problem of a polaron in quantum dot is retrieved using a modified LLP approach. The modification is intended to interpolate between the strong- and the weak-coupling limits of the problem. The polaronic effect is found to be more important for small dot sizes.